Japanese art: transcultural perspectives - Trede, Melanie; Wakita, Mio; Guth, Christine (Studies in Asian art and archaeology, 2025)
"The transcultural approach to Japanese art history embraced by the contributors to this volume centers on the dynamic aesthetic, artistic, and conceptual negotiations across cultural, temporal, and spatial boundaries. It not only acknowledges material objects, people, and technologies as agents, but also intangible practices such as knowledge and concepts as vital agencies of interaction in transcultural processes. With its premise on connectivity, trans-territoriality, networks, and their transformative potential, this research destabilizes categorical configurations such as "center vs. periphery" and "high vs. low," calling into question the classical canon of Japanese art history"
Keywords: Aufsatzsammlung; Geschichte; Kulturaustausch; Kunst; Japan